2015
DOI: 10.1097/cji.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Clinical Trial of CD1c (BDCA-1)+ Dendritic Cells Pulsed With HLA-A*0201 Peptides for Immunotherapy of Metastatic Hormone Refractory Prostate Cancer

Abstract: Preclinical studies have suggested that purified populations of CD1c (BDCA-1) blood-derived dendritic cells (BDC) loaded with tumor-specific peptides may be a feasible option for prostate cancer immunotherapy. We performed an open-label dose-finding Phase I study to evaluate the safe use of CD1c BDC in patients with advanced metastatic hormone refractory prostate cancer. HLA-A*0201-positive patients with advanced metastatic prostate cancer were recruited and consented. The vaccine was manufactured by pulsing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 5 publications
0
74
0
Order By: Relevance
“…1 Initial clinical studies have shown that immune selected BDC preparations are safe and able to induce clinical responses in patients. 19,22 , 43 The readily obtained CMRF-56 C BDC preparation described here was enriched for all myeloid BDC subpopulations and these were shown to have the expected intrinsic migration capacity, without the need for modulatory compounds such as PGE 2 . Furthermore, we found that these BDC were also superior to Mo-DC with respect to their ability to process and present mRNA antigens for MHC presentation to T cells.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…1 Initial clinical studies have shown that immune selected BDC preparations are safe and able to induce clinical responses in patients. 19,22 , 43 The readily obtained CMRF-56 C BDC preparation described here was enriched for all myeloid BDC subpopulations and these were shown to have the expected intrinsic migration capacity, without the need for modulatory compounds such as PGE 2 . Furthermore, we found that these BDC were also superior to Mo-DC with respect to their ability to process and present mRNA antigens for MHC presentation to T cells.…”
Section: Discussionmentioning
confidence: 96%
“…The density gradient separation methodology used in Sipuleucel-T 44-46 enriched for low-density cells, but only 18% of these were CD54 C HLA-DR C cells, 46 and of these, only a small proportion were BDC. Magnetic bead immune selection of individual populations of CD1c C mDC 19,20 or CD304 C pDC 22 is starting to be explored in clinical trials. The generic platform used in this study built on previous work with the original mouse IgG1 CMRF-56 mAb 47 by developing a clinically suitable hCMRF-56 mAb to enrich for a similar heterogeneous BDC population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations